PC magazine windows XP solutions - Randall, Neil (Wiley, 2006)
From the #1 source for computing information, trusted by more than six million readers worldwide. Shows Windows users how to turn off features they don't want, clean up the Registry after an uninstall, safely remove old drivers, use the Recovery Console after a crash, and much more. Packed with authoritative advice and instruction, this latest edition includes more than 100 pages of new coverage and provides insight and suggestions for hundreds of third party tools and software for Windows XP. New sections are the result of feedback from readers who asked for additional coverage of security, fighting spyware, disaster recovery, and more